Elastic-plastic stress investigation on crack branching in fibre-reinforced composites - Hussain, Naveeda (2017)
The increasing demand for fiber reinforced composites (FRCs) in many manufacturing industries has propelled the need to refine and improve existing knowledge on the properties of these materials. Valued for their high strength and versatility, existing defects on FRCs may eventually cause catastrophic mechanical failures. Thus, a thorough understanding and review of the principles behind failure in FRCs is crucial. This project employed finite element analysis software ABAQUS 6.16 to simulate the interaction between an existing crack and circular inclusion on an infinite matrix under mode-I opening displacement. The elastic-plastic stress analysis was based on failure characteristics such as Stress Intensity Factors and Crack Tip Opening Displacements. Analysis showed that crack propagation is greatly affected by matrix-inclusion elastic modulus strength with a softer inclusion experiencing the greatest stresses. The effect of varying inclusion diameter, crack-inclusion distance and crack orientation was also investigated in relation to the tendency for crack to propagate at various dimensions. It was later found crack tips that were closer to a large inclusion or branched at the smaller angle tended to have greater stresses under elastic condition or CTOD under plastic condition. Keywords: Crack displacement mode; Stress Intensity Factor; J-Integral; Crack Tip Opening Displacement.